Intra- and inter-regional research collaboration across organizational boundaries: evolving patterns in China - Sun, Yutao; Cao, Cong (Elsevier, 2015)
Both intra-regional and inter-regional research collaboration are significant determinants for regional innovation. However, systematic and empirical studies have seldom been reported integrating both of them. The present study advances a research agenda around a two-dimensional quadrant (TDQ) analytical framework to investigate regional research collaboration. It then applies such a framework to the Chinese case by examining collaborative invention patent applications between 1985 and 2008 with China’s patent office. The results show that, first, the correlation between innovation capability and collaborative research is evolving, and the correlation between innovation capability and collaboration between enterprises (EE) is weaker than that between academic institutes and enterprises (AE); second, the intra-regional collaboration intensity was higher than the inter-regional and AE collaboration dominated the regional collaboration; third, during the process of market-oriented reform, China’s major innovative regions with different collaborative patterns were shifting from collaborative to independent research, from inter-regional collaboration to intra-regional collaboration, and from AE to EE collaboration, particularly in their inter-regional collaboration.